2009
DOI: 10.1186/1471-2474-10-166
|View full text |Cite
|
Sign up to set email alerts
|

Articular cartilage mineralization in osteoarthritis of the hip

Abstract: BackgroundThe aim of this study was to examine the frequency of articular cartilage calcification in patients with end-stage hip OA. Further, its impact on the clinical situation and the OA severity are analyzed.MethodsEighty patients with OA of the hip who consecutively underwent total hip replacement were prospectively evaluated, and 10 controls were included. The patients' X-rays were analyzed for the presence of articular cartilage mineralization. A Harris Hip Score (HHS) was preoperatively calculated for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
54
0
8

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 20 publications
5
54
0
8
Order By: Relevance
“…Articular cartilage calcification is associated with severe osteoarthritis (OA) and destructive arthropathies, such as Milwaukee shoulder syndrome. Interestingly, BCP crystals are detected in 100% of knee and hip osteoarthritic cartilages harvested at the time of total joint arthroplasty (1,2). BCP crystal deposition in knee articular cartilage is correlated with cartilage destruction and more severe lesions (1).…”
mentioning
confidence: 99%
“…Articular cartilage calcification is associated with severe osteoarthritis (OA) and destructive arthropathies, such as Milwaukee shoulder syndrome. Interestingly, BCP crystals are detected in 100% of knee and hip osteoarthritic cartilages harvested at the time of total joint arthroplasty (1,2). BCP crystal deposition in knee articular cartilage is correlated with cartilage destruction and more severe lesions (1).…”
mentioning
confidence: 99%
“…A similar study by the same group showed that BCP deposits also occurred in hip OA cartilage, further emphasizing the generalization of the cartilage mineralization process during OA (14). However, the exact role of BCPs in OA cartilage destruction has yet to be investigated.…”
Section: To the Editormentioning
confidence: 69%
“…These include the perichondrocytic degradation of the cartilage matrix by aforementioned proteases but also cartilage mineralization. Cartilage mineralization is of interest because recent data suggest that in human osteoarthritis (OA), mineralization of cartilage is re-initiated as part of the pathogenic changes associated with the terminal, hypertrophic differentiation of diseased chondrocytes [80,81]. While in healthy articular cartilage most chondrocytes maintain a stable resting phenotype and resist proliferation and differentiation, articular chondrocytes from osteoarthritic joints form clusters by proliferating more strongly and eventually develop hypertrophy, typically close to areas of mineralized cartilage matrix and near sites of surface lesions [40,82].…”
Section: Changes In Chondrocyte Metabolismmentioning
confidence: 99%
“…While in healthy articular cartilage most chondrocytes maintain a stable resting phenotype and resist proliferation and differentiation, articular chondrocytes from osteoarthritic joints form clusters by proliferating more strongly and eventually develop hypertrophy, typically close to areas of mineralized cartilage matrix and near sites of surface lesions [40,82]. Recent evidence suggests that hypertrophic chondrocytes in the growth plate and in osteoarthritic cartilage share certain similarities, and that the calcification of hyaline cartilage is a regular event in human OA [81,83]. One key finding linking chondrocyte hypertrophy to similar mechanisms involved in endochondral ossification is the expression of HIF-2 alpha during both processes.…”
Section: Changes In Chondrocyte Metabolismmentioning
confidence: 99%
See 1 more Smart Citation